(3YfhGf GdoeQbUGJ hGdoeWQHGJs - (3Ydj Hf ehSi Hf eMeO Hf YHO Gdedc GHf SYjO, GdYfSj GdeOdLj GdeZQHj , CHh GdMSf, fhQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj TQa GdEfSGf, Ydi SGFQCfhGY GdMjhGf s
(3BNQgG (B:s
(3Hjf GdSjha hYjfjg eTGQcI ef CLdgG bjd ddCZeGO CLaGf s
(3HgG fXGe GdJYbjHIs
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B54 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1658s
Keywords: (3GdCOHs